Coordinated Control Schemes for Improved DER Hosting Capacity and Flexibility Provision - Laaksonen, Hannu; Khajeh, Hosna; Hatziargyriou, Nikos (Institution of engineering and technology, 2024)
In the future, efficient utilization of all potential flexible energy resources from different voltage levels is needed to fulfill simultaneously the flexibility needs of local distribution system operator (DSO) and system-wide transmission system operator (TSO) in a coordinated way. This paper studies coordinated and frequency level-dependent distributed energy resources’ (DERs’) control and adaptive on-load-tap-changer (OLTC) management scheme to enable prioritized flexibility services provision for the DSOs and TSO. The main idea is that the coordination of flexibilities utilization between distribution and transmission system operators is done depending on the frequency deviation severity. During smaller frequency deviations priority is on DSO needs and during larger frequency deviations priority is on TSO needs in order to support the frequency stability of the whole power system. However, the overall target is to increase DERs’ hosting capacity in the DSO network and increase their availability for the TSO flexibility services provision during the smaller frequency deviations. In this paper, the effect of different DERs’ reactive power control schemes, their location and type of distribution feeders are studied with multiple PSCAD simulations.
Keywords: distributed power generation; hosting capacity; flexibility services; DSO-TSO coordination; active network management; fi=Sähkötekniikka|en=Electrical Engineering|